Transport and dispersion of tritium from the radioactive water of the Fukushima Daiichi nuclear plant. (August 2021) - Zhao, Chang; Wang, Gang; Zhang, Min; Wang, Guansuo; de With, Govert; Bezhenar, Roman; Maderich, Vladimir; Xia, Changshui; Zhao, Biao; Jung, Kyung Tae; Periáñez, Raúl; Akhir, Mohd Fadzil; et al.
Abstract: Japan recently announced plans to discharge over 1.2 million tons of radioactive water from the Fukushima Daiichi Nuclear Power Plant (FDNPP) into the Pacific Ocean. The contaminated water can poses a threat to marine ecosystems and human health. To estimate the impact of the plan, here, we developed a three-dimensional global model to track the transport and dispersion of tritium released from the radioactive water of the FDNPP. The pollution scenarios for four release durations (1 month, 1 year, 5 years, and 10 years) were simulated. The simulation results showed that for the release in short-duration scenarios (1 month and 1 year), the peak plume with high tritium concentration shifted with the currents and finally reached the northeastern Pacific. For the long-duration scenarios (5 years and 10 years), the peak plume of the contaminated water was confined to coastal regions east of Japan. Highlights: The spatiotemporal transport of tritium seawater released from FDNPP is simulated. Radioactive seawater arrives at the Pacific coast of North America within 4 to 5 years. The released tritium seawater expands into the China Seas in 2–3 years.